PARAMETERS OF PROTEIN METABOLISM IN GOATS FED DIETS WITH DIFFERENT PORTION OF SUGARCANE BAGASSE - Ariyani, S.A.; Nuswantara, L.K.; Pangestu, E.; Wahyono, F.; Achmadi, J. (Journal of the Indonesian Tropical Animal Agriculture, 2014)
Fifteen Jawarandu male goats were used to study the effect of different portion of sugarcanebagasse in diets on some parameters of protein metabolism. Goats had average of body weight of 18 kgand aged at 18 months. Animals were housed in metabolic cages and were alloted to a completelyrandomized design receiving three experimental diets with sugarcane bagasse portions of 15, 25, and35% (dry matter basis), respectively. After eight weeks of adjustment period to experimental diets andenvironment, each group of treatment was subjected to ten days of digestion trial, and followed bycollection of rumen liquid samples. Parameters observed were feed digestibility, nitrogen retention,ruminal feed fermentation, and excretion of urinary allantoin to estimate microbial protein synthesis.Data were tested using one way analysis of variance, and followed by Duncan’s mulitiple range test. Drymatter and protein intakes lowered (P<0.05) as the increasing of sugarcane bagasse in diets. Proteindigestibility and retention were unaffected by the treatment of bagasse portion. The dietary treatment didnot change ruminal ammonia, total VFA, acetate, propionate, and butyrate concentrations. Microbialnitrogen synthesis and efficiency of microbial nitrogen synthesis were unaffected by the dietarytreatment.